Tungsten-Promoted Hetero-Pauson–Khand Cycloaddition: Application to the Total Synthesis of (–)-Allosecurinine - Chirkin, Egor; Bouzidi, Chouaha; Porée, François-Hugues (Synthesis, 2019)
Herein, we report a concise enantioselective synthesis of (–)-allosecurinine, a tetracyclic Securinega alkaloid featuring an α,β-unsaturated γ-lactone moiety. Starting from inexpensive and readily available trans-l-hydroxyproline, our strategy entails a rare late-stage [2+2+1]-hetero-Pauson–Khand cycloaddition between a ketone and an alkyne as the key complexity-generating step to rapidly install the CD-ring system. The reported W(CO)6-promoted intramolecular cyclization provides the first example of a tungsten-mediated hetero-Pauson–Khand reaction. This approach to the strained bicyclic CD motif present in allosecurinine provides some insights into the boundaries of this potentially powerful methodology that might be further extended to other butenolide-containing natural products.
Keywords: alkaloids; total synthesis; tungsten; cyclization; natural products